FICTIONAL TEXT AS A CULTURAL UNIT - Komila Rasulova (Journals Park Publishing, 2025)
This article explores the concept of fictional texts as vital cultural units that both reflect and shape the values, beliefs, and social norms of the societies from which they emerge. Fictional narratives serve as repositories of cultural knowledge, offering insights into collective identities, historical contexts, and ideological frameworks. The study examines how fictional texts function as mediums for cultural expression and transmission, bridging past and present, and facilitating intercultural understanding. The article also discusses the role of fiction in preserving cultural heritage and influencing societal change, emphasizing its significance in the ongoing dialogue between tradition and innovation. Through interdisciplinary analysis, the article highlights the importance of fictional texts as dynamic cultural artifacts that contribute to the continuous construction and negotiation of cultural identity.
Keywords: Fictional text, culture, literary text, cultural values, notion, national vision, society.